Optimism and pessimism in games - Eichberger, Jürgen; Kelsey, David (Department of Economics discussion papers, 2009)
This paper considers the impact of ambiguity in strategic situations. It extends the earlier literature by allowing for optimistic responses to ambiguity. Ambiguity is modelled by CEU preferences. We propose a new solution concept for players who may express ambiguity-preference. Then we study comparative statics of changes in ambiguity-attitude in games with strategic complements. This gives a precise statement of the impact of ambiguity on economic behaviour.
Keywords: Arbeitspapier; Graue Literatur